Who cares? Future sea-level-rise and house prices - Olga Filippova; Cuong Nguyen; Ilan Noy; Michael Rehm (Center for Economic Studies and ifo Institute (CESifo), 2019)
Globally, the single-most observable, predictable, and certain impact of climate change is sea level rise. Using a case study from the Kapiti Coast District in New Zealand, we pose a simple question: Do people factor in the warnings provided by scientists and governments about the risk of sea-level rise when making their investment decisions? We examine the single most important financial decision that most people make – purchasing a home, to see whether prices of coastal property change when more/less information becomes available about property-specific consequences of future sea level rise. The Kapiti Coast District Council published detailed projected erosion risk maps for the district's coastline in 2012 and was forced to remove them by the courts in 2014. About 1,800 properties were affected. We estimate the impact of this information on home prices using data from all real estate transactions in the district with a difference-in-differences framework embedded in a hedonic pricing model. We find that the posting of this information had a very small and statistically insignificant impact on house prices, suggesting people do not care much about the long-term risks of sea-level rise as they do not incorporate these risks in their investment decisions.
Keywords: Q54; R38; 330; house price; sea level rise; climate change; erosion